Gut Microbiota in Heart Failure Patients With Preserved Ejection Fraction (GUMPTION Study) - Huang, Ziyin; Mei, Xiaofei; Jiang, Yufeng; Chen, Tan; Zhou, Yafeng (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Heart failure with preserved ejection fraction (HFpEF) is associated with disrupted intestinal epithelial function, resulting from intestinal congestion. Intestinal congestion changes the morphology and permeability of the intestinal wall, and it becomes easy for the gut microbiota to change and transfer. Intervention on gut microbiota may become a new target for HFpEF treatment. However, the characteristics of gut microbiota in patients with HFpEF remain unknown. This preliminary report aims to detect the structure of gut microbiota in HFpEF patients so as to explore their characteristic changes, thereby providing a theoretical basis for future research. Methods: This research recruited 30 patients diagnosed with HFpEF and 30 healthy individuals. Stool specimens of research subjects were collected separately, and the microarray analyses of gut microbiota were conducted by Illumina high-throughput DNA sequencing. The differences in gut microbiota composition, alpha diversity, and beta diversity between the two groups were finally obtained. Results: The composition of gut microbiota was significantly different between the two groups. At the phylum classification level, the abundance of Synergistetes tended to be higher in the HFpEF group (P = 0.012). At genus classification level, the abundance of Butyricicoccus (P < 0.001), Sutterella (P = 0.004), Lachnospira (P = 0.003), and Ruminiclostridium (P = 0.009) in the HFpEF group were lower, while the abundance of Enterococcus (P < 0.001) and Lactobacillus (P = 0.005) were higher. According to the Chao index of alpha diversity analysis, HFpEF patients showed a nominally significant lower species richness when compared with controls (P = 0.046). However, there was no statistical difference in the Shannon index (P = 0.159) and Simpson index (P = 0.495), indicating that there was no difference in species diversity between the two groups. Beta diversity analysis revealed a highly significant separation of HFpEF patients and controls. Conclusions: An imbalance in the gut microbiota of HFpEF patients was observed. Patients with HFpEF have an increased abundance of microbiota associated with inflammation and a decreased abundance of microbiota associated with anti-inflammatory effects in the gut environment. In line with that, the species richness of gut microbiota in HFpEF patients tended to be lower.